A COMPARATIVE STUDY ON THE EFFICACY AND SAFETY OF TENELIGLIPTIN VERSUS GLIMEPIRIDE AS AN ADD-ON THERAPY TO METFORMIN MONO-THERAPY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Shivam; Nadig, Pratibha; H A, Vijaya Sarathi; KN, Manohar (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Type 2 Diabetes Mellitus (T2DM) represents a heterogeneous condition characterized by hyperglycemia as a consequence of defects in insulin secretion, insulin resistance/action or combination of both of these factors. Sulfonylureas are very efficacious and are recommended as second line drugs for treatment in T2DM. Dipeptidyl peptidase-4 inhibitors (DPP-4i) have demonstrated efficacy and safety in patients with inadequate glycaemic control with metformin mono-therapy. METHODOLOGY This study was conducted at Endocrinology department at Vydehi Institute of Medical Sciences and Research Center, Bangalore, Karnataka, India after institutional ethics committee approval from January 2017 to December 2017. A total of 40 patients were randomized into two groups after obtaining written informed consent. Group A received Tab. Metformin 1 gm twice a day along with a Tab. Teneligliptin 20 mg once a day and Group B received Tab. Metformin 1 gm twice a day along with Tab. Glimepiride 1 mg once a day for a period of 12 weeks. RESULTS There was significant difference in mean HbA1c between two groups at 12 weeks. At Week 12 weeks Mean HbA1c was significantly lower in Glimepiride Group than in Teneligliptin Group. Fasting Plasma Glucose and Post Prandial Plasma Glucose were significantly lower in Glimepiride Group than in Teneligliptin Group. The incidence of adverse effects was more in Teneligliptin group (constipation). CONCLUSION The present study showed that addition of glimepiride apart from improving the baseline glycosylated hemoglobin (HbA1c) also led to significant reduction in fasting, post prandial plasma glucose levels, lipid profiles and is well tolerated as compared to Teneligliptin.